Why a Bank Should be Bailed Out: A Theoretical Model and Case Study From Indonesia - Aprianti, Kartika Sofia (2016)
This study highlights three criteria of why a bank should be bailed out which are “too big to fail”, “too business connected to fail”, and “too similarity connected to fail”. Using graph theory and Bayes theorem, we explore the transmission process of shock happened in one bank throughout the entire financial system. Our findings show that “too big to fail” should not be used as the criterion for bailout decision as a financial institution can grow larger without increasing its systemic importance. Meanwhile, the policymaker should not bailout a bank considered as “too business connected to fail” institution as it is possible that the system could withstand by itself due to the good transmission process of losses. Further, we raise the discussion of two similarity dimensions in the context of informational contagion. We found that sufficiently similar banks could be adjacent to each other which results in the other banks to be more reachable to have the contagion. We extend our findings to analyze the case of Century Bank which remains questioned by the public. Considering our analysis, we find that Century Bank was deserved to be bailed out due to the interconnectedness and similarity criteria. Our results have raised important recommendations for the policymaker regarding the bailout policy.